PENINGKATAN UMUR SIMPAN FILET IKAN DENGAN PELAPIS EDIBLE YANG DIINKORPORASI EKSTRAKS KASAR OVOCLEIDIN-17 - Warkoyo Warkoyo; Nanda Zuhriansyah (Jurnal Perikanan Universitas Gadjah Mada, 2014)
Fish ﬁ llet as protein based food will susceptible to damage when stored at room temperature without any treatment. The shelf life of ﬁ sh ﬁ llet at room temperature only just 12 hours. The effort that public have been made to extend it in storage and transport is a cooling system. To reduce the dependency on the ice usage is needed a way or method to be applied, namely active packaging. Some publications mention that the active packaging can inhibit microbial growth on the ﬁ sh ﬁ llet. The purpose of this study was to determine the inﬂ uence of edible coatings were incorporated ekstraks rough Ovocleidin 17 (EKO-17) on the quality of ﬁ sh ﬁ llets during storage. This study was conducted using a randomized block design with three replications simple. Factors to be tested is EKO-17 concentration in edible coatings. The parameters observed in this study is total microbial, TVB-N, protein content, and heavy losses. The results showed that the concentration of EKO-17 signiﬁ cantly affect the total microbial, TVB-N and protein content. EKO-17 concentration of 0.9% with room temperature storage for 27 hours gives the best results, the total microbial 7,27 (106 CFU / g), the TVB-N 17.02 mg / 100 g, protein content of 10.75%, severe shrinkage of 0.43%.